Relationship between Father Involvement in Parenting and Adolescent Mental Health - Rajab, M. Alfian; Toban, Rindani Claurita; Yuliandini, Astri; Ramadani, Nadia Frisilia (Genius Journal, 2026)
Introduction: Adolescence is a critical developmental stage that is vulnerable to mental health problems. Globally, about 14% of adolescents experience mental health issues, and in Indonesia, the prevalence reaches 34.9%. A study in Makassar City also revealed that 47.9% of adolescents aged 15–18 years suffer from mental health problems. Family factors, particularly father involvement in parenting, play an important role in maintaining adolescent mental health. Objective: To analyze the relationship between father involvement in parenting and adolescent mental health. Method: This quantitative study employed a descriptive analytic design with a cross-sectional approach. The sample consisted of 78 tenth-grade students at SMA Negeri 3 Makassar. Data were collected using questionnaires on father involvement and adolescent mental health, and analyzed using the Chi-square test. Result: Most respondents were female (65.4%) and aged 15 years (61.5%). Adolescent mental health levels were categorized as very good (26.9%), good (59%), and poor (14.1%). Father involvement was mostly at the moderate level (70.5%), followed by high (17.9%) and low (11.5%). The Chi-square test showed a p-value of 0.000, indicating a significant relationship between father involvement in parenting and adolescent mental health. Conclusion: Father involvement in parenting has a significant impact on adolescent mental health. Higher father involvement is associated with better adolescent mental well-being. Strengthening the role of fathers, both emotionally and physically, is essential to support adolescents’ psychological well-being.